A method of optimizing the structure of hierarchical distributed control systems - Onufrey, A.Yu; Razumov, A.V.; Kakaev, V.V. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
A description of the control system represented in the form of an oriented graph and a method for formalization of the problem of choosing a variant of the control system structure are proposed. The research results of hierarchical distributed control systems based on analytical and statistical models for evaluating performance indicators and optimizing their structure are presented. A model and a method for optimization control systems with a hierarchical structure have been developed which makes it possible to optimize a control system with an arbitrary structure based on the synthesis of a reference variant of a homogeneous hierarchical structure. In comparison with the known methods, the assumption of uniformity of the structure of the control system makes it possible to use an analytical solution when choosing a reference plan in accordance with the proposed criterion in the vector space “efficiency-cost”. The proposed optimization method is based on proofing the possibility to analytically investigate homogenous hierarchical distributed control systems and on establishing the dependency of the cost and time of task solving in the control system on the structure parameters. The method for optimizing the structure in hierarchical distributed control systems consists of two main stages. At the first stage, within the framework of the analytical model, the direct optimization problem is solved by minimizing the processing time with a cost constraint and the inverse optimization problem is solved by minimizing the cost with a processing time constraint. The result is the choice of the best reference plan for a homogeneous control system structure. At the second stage, based on simulation modeling, the problem of determining the “critical” areas (control points) that limit the effectiveness of the control system is solved. The found “critical” areas are subject to improvement by changing their structure and introducing new technical solutions that provide the specified performance indicators of the entire management system. A model of the hierarchical structure of the management system is given. The procedure for selecting the reference variant and the algorithm for modifying the structure of the control system are shown. An example of optimizing the structure of the control system is given according to the criterion of the required throughput. The example showed that the application of the proposed method allows choosing a variant of the structure of the control system that satisfies the selected criterion and the specified constraints. It is advisable to apply the proposed method at the early stages of designing distributed information control systems when choosing variants of their construction and substantiating requirements for the technical characteristics of structural elements.